Some pottery productions from the kilns of Vingone in Scandicci (Florence/Italy) - Fabbri, Fabiana (Rei Cretariae Romanae Fautorum Acta, 2024)
The Vingone kilns area, working during the early imperial period, was brought to light by the Soprintendenza ai Beni archeologici della toscana in the eighties of the 20th century under a large building site in the country near Scandicci, south-west of the city of Florence, in tuscany. Besides bricks and amphoras, the kilns produced a considerable amount of different kinds of vessels: thin-walled pottery, grey ware and a wide range of common ware and coarse ware including objects to be referred to domestic or cult furnishing. A complete study concerning the kilns and their productions has recently been published. This article will discuss some of the most remarkable ceramic vessels the current writer was appointed to study: thin-walled pottery, common ware, coarse ware and objects to be referred to domestic or cult furnishing.